STUDY ON INCREASING THE CORROSION RESISTANCE OF ALUMINUM ALLOYS BY FSP/SFSP PROCESSING - Lavinia Ileana Sirbu; Lia Nicoleta Botila; Gabriela Victoria Mnerie (Nonconventional Technologies Review)
The work considers an analysis of some studies and researches carried out internationally regarding the improvement of the corrosion resistance of aluminium alloys through FSP/SFSP processing. The study investigates the increase in corrosion resistance of aluminium processed by friction stir processing in various working environments. The paper aims to identify the parameters of the technological process that influence the increase in corrosion resistance and the improvement of the metallic properties of aluminium alloys. The obtained findings will contribute to the expansion of the use of aluminium alloy processing technology in various industrial applications exposed to corrosive environments.